(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, criminals are getting wiser and better; in that case, we need to cope and think of an immediate solution to help our city because now criminals innovate a new plan and new modus operandi to execute their bad acts and successfully finish them. The primary aim of this study is to provide information regarding the use of the Facebook platform in providing crime information campaigns in North Fairview Quezon City. The study presents data on the demographic profile of the respondents, assessment of the respondents to Facebook as a provider of crime information campaign, problems encountered by the Police officer in terms of legality of the post, acceptance of the end user, and availability of information and the statistical tool used were frequency and percentage, weighted mean, and Likert scale. Based on the data, the majority of the respondents are male and single, aged 31 and above. In terms of the assessment by the end-user on Facebook, the legality of the post is considered the most effective in providing factual information. Acceptance of the end user is considered to create a connection to the community, and availability of information is considered to spread information efficiently. Overall, the respondents Strongly Agree that Facebook is an effective way to provide crime information campaigns. Based on the findings of the study, it is recommended that law enforcement agencies and other organizations responsible for crime information campaigns on social media platforms should take into account the perceptions of both citizens and police officers to design more effective campaigns. The law enforcement who are responsible for disseminating crime information campaigns should innovate more ways to disseminate campaigns faster to the community in order to make them more accessible.